Relationship between Job Stress with Menstrual Bleeding Pattern among Midwives - Soheila Mohamadirizi; Masoumeh Kordi; Mohamad Taghi Shakeri; Javad Salehi Fadardi; Leili Hafizi (Tehran University of Medical Sciences, 2013)
Background & Aim: Job stress can interfere with endocrine function and result in dysfunctional menstrual bleeding patterns. The aim of this study was to assess the relationship between job stress with menstrual bleeding pattern among midwives. Methods & Materials: In this cross-sectional study, we recruited 150 midwives working in hospitals and health centers of Mashhad using two-stage sampling. Data were collected using a questionnaire including demographic characteristics, Karazek Job Content, a daily diary for menstrual periods to record duration and interval of periods, and the Higham Chart for recording the bleeding amount. The diary was completed for three menstrual periods. Collected data were analyzed using independent t-student, one way ANOVA, Mann-Whitney U, Chi-squared test, correlation test and linear regression in the SPSS-14. Results: The findings showed that 21.3% of the midwives reported mild job stress, 19.3% had moderate stress and 59.3% reported severe job stress. Mean of the duration of the periods was 7.06 days, the mean interval of the periods was 27.9 days and the mean amount of bleeding was 79.72 cc. There was a significant relationship between job stress and the duration and interval of periods (P<0.001). There was not any significant relationship between job stress with the amount of bleeding. Conclusion: Our study showed that job stress was related to menstrual bleeding patterns among midwives. It is necessary introduce strategies to decrease job stress and provide professional support for midwives.